2015
DOI: 10.1371/journal.pone.0124796
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylases Facilitates Extinction and Attenuates Reinstatement of Nicotine Self-Administration in Rats

Abstract: Chromatin remodelling is integral to the formation of long-term memories. Recent evidence suggests that histone modification may play a role in the persistence of memories associated with drug use. The present series of experiments aimed to examine the effect of histone deacetylase (HDAC) inhibition on the extinction and reinstatement of nicotine self-administration. Rats were trained to intravenously self-administer nicotine for 12 days on a fixed-ratio 1 schedule. In Experiment 1, responding was then extingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…Similar methods have been used by others (Berglind et al 2007; Castino et al 2015; Fuchs et al 1998, 2005; Venniro et al 2016). …”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Similar methods have been used by others (Berglind et al 2007; Castino et al 2015; Fuchs et al 1998, 2005; Venniro et al 2016). …”
Section: Methodsmentioning
confidence: 87%
“…One of few studies to investigate the effects of HDACi on operant drug extinction found that a post-extinction injection (IP) of a class I inhibitor (NaB) decreased nicotine-seeking during cued-extinction (one day after treatment), that at least six days of post-extinction treatment decreased the time it took to reach extinction criterion, and weakened reinstatement (Castino et al 2015). This effect supports our results with post-session delivery, with faster rates of extinction criterion reached in the RGFP966-treated rats compared to vehicle-treated rats in our studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study shows that mice receiving NaB injections immediately after extinction trainings extinguished METH‐induced CPP both faster and to a greater extent than saline‐treated mice. It is important to emphasize that the extinction of CPP not only is involved in the extinction of already established addictive memory but also initiated the process of extinction memory, which also requires the activation of gene transcription (Alberini, ; Bouton et al, ; Castino et al, ). Therefore, a possible explanation for our results is that NaB facilitated the consolidation of extinction memory by enhancing the transcription of genes required for the formation of memory.…”
Section: Discussionmentioning
confidence: 99%
“…after a drug‐primed reinstatement test), (2) where behavioural performance will be equivalent (level of responding is similar across groups on the final day of extinction) and (3) following a procedure that leads to a significant attenuation of subsequent reinstatement in NaB‐treated rats (Castino et al . ).…”
Section: Methodsmentioning
confidence: 97%